Structured flexibility in assessment: students’ perceptions of the impact of different elements of choice on their decision making, engagement, and learning experiences - Hills, Melissa; Copland, Sarah; McKendrick-Calder, Lisa (My University, 2025)
Research on the learning- and engagement-related impacts of choice in assessment is growing, though it often focuses on a single kind of choice with insufficient attention to the learning priorities and motivations behind students’ decisions. The assessment design explored here offered flexibility to students by providing multiple kinds of choice while maintaining the critical structure of a single type of assignment, which was necessary to preserve learning outcomes and not overwhelm students. This study investigated the impact of choice not only on students’ perceptions of their learning and engagement but also on their decision making process in order to better understand their motivations and the influences of learning priorities and individual circumstances. Guided by a mixed methods approach involving a survey followed by interviews, we found that offering choice in assessment increased students’ perceived autonomy and control, ability to balance other demands, quality of work, and enjoyment and interest in the work, while decreasing their stress levels. We also found that offering multiple elements of choice in a single assessment supported students’ abilities to make decisions based on their complex and diverse learning priorities, motivations, and individual circumstances. This study, as well as research on flexible assessment more broadly, respond to the International Society for the Scholarship of Teaching and Learning’s grand challenges, which include a call for more investigation into student engagement in learning and the complex processes of learning.
Keywords: assessment; flexibility and choice; student engagement and learning; grand challenges; mixed methods